PnAn13, an antinociceptive synthetic peptide inspired in the Phoneutria nigriventer toxin PnTx4(6–1) (δ-Ctenitoxin-Pn1a). (September 2020) - Emerich, Bruna Luiza; Ferreira, Renata Cristina Mendes; Machado-de-Avila, Ricardo Andrez; Resende, Jarbas Magalhães; Duarte, Igor Dimitri G.; de Lima, Maria Elena
Abstract: Animal venoms are an almost inexhaustible source for promising molecules with biological activity and the venom of Phoneutria nigriventer spider is a good example of this. Among several other toxins obtained from this venom, PnTx4(6–1), also called δ-Ctenitoxin-Pn1a, was isolated and initially described as an insect toxin that binds to the site 3 of sodium channels in cockroach nerve cord synaptosomes ( Periplaneta americana ) and slows down sodium current inactivation in isolated axons of this animal. This toxin did not cause any apparent toxicity to mice when intracerebroventricularly injected (30 μg). Subsequently, it was demonstrated that PnTx4(6–1) has an antinociceptive effect in three different pain models: inflammatory, induced by carrageenan; nociceptive, induced by prostaglandin E2 and neuropathic, induced by sciatic nerve constriction. Using diverse antagonists from receptors, it was shown that the cannabinoid system, via the CB1 receptor, and the opioid system, through the μ and δ receptors, are both involved in the antinociceptive effect of PnTx4(6–1). In the present work, it was synthesized a peptide, named PnAn13, based on the amino acid sequence of PnTx4(6–1) in order to try to reproduce or increase the analgesic effect of the toxin. As it was seen for the toxin, PnAn13 had antinociceptive activity, when intrathecally injected, and this effect involved the cannabinoid and opioid systems. In addition, when it was evaluated the peripheral effect of PnAn13, via intraplantar administration, this peptide was able to reverse the hyperalgesic threshold, evoked by prostaglandin E2 . Therefore, using different pharmacological tools, it was shown the participation of cannabinoid and opioid systems in this effect. Highlights: A synthetic peptide PnAn13, reproduced the antinociceptive effects of the PnTx4(6-1) (δ-Ctenitoxin-Pn1a) toxin. PnAn13 showed a clear analgesic effect in the nociceptive in vivo rat pain model, both centrally and peripherally. The antinociceptive effect of PnAn13 involves cannabinoid and opioid systems.